Closer to the Site of Action: Everolimus Concentrations in Peripheral Blood Mononuclear Cells Correlate Well With Whole Blood Concentrations. Issue 5 (October 2015) - Robertsen, Ida; Vethe, Nils Tore; Midtvedt, Karsten; Falck, Pål; Christensen, Hege; Åsberg, Anders
Abstract : Background: Everolimus (EVE) is an immunosuppressive drug dosed according to therapeutic drug monitoring in renal transplant recipients. The primary site of action is within activated lymphocytes. EVE is a substrate of the efflux transporter ABCB1 also known as P-glycoprotein. Limited data exist regarding a possible association between whole blood and intralymphocyte concentrations of EVE and the potential influence of ABCB1. Methods: Twelve renal transplant recipients (5 men and 7 women) treated with EVE underwent a pharmacokinetic investigation where EVE concentrations in whole blood and in peripheral blood mononuclear cells (PBMC) were determined within a dosing interval. In addition, the activity of ABCB1 in PBMC was determined using the Rhodamine123 efflux assay and the patients' genotypes of ABCB1 were determined. Results: There was a significant correlation between EVE AUC0–12 in whole blood and in PBMC (r = 0.90, P < 0.01), and no association was demonstrated between the ABCB1 activity and EVE PBMC/whole blood ratio of trough concentrations (r = 0.23, P = 0.76). Furthermore, ABCB1 1236C>T, 3435C>T, and 2677G>T/A polymorphism did not influence EVE AUC0–12 PBMC/whole blood ratio. Conclusions: The results revealed a significant association between EVE whole blood and PBMC concentrations, suggesting that ABCB1-mediated efflux from PBMC to be of minor importance for the distribution of EVE.